2022
DOI: 10.1002/ep.14022
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted exfoliation of graphite using 1‐allyl‐pyridinium‐based ionic liquids and application to solid acid catalysts

Abstract: A novel, eco‐friendly direct graphite exfoliation method was developed using 1‐allyl‐pyridinium‐based ionic liquids (ILs) under microwave irradiation. Exfoliated graphene comprising a few layers was prepared from graphite using 1‐allyl‐pyridinium nitrate under 300 W microwave irradiation for 10 min, which was characterized by X‐ray diffraction, Raman spectroscopy, and X‐ray photoelectron spectroscopy. Density functional theory calculations indicated that the combination of the cations and anions in the ILs led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The authors ascribed the success of the MAIL technique to the decomposition of PF 6 − -containing ILs accompanied by the generation of hydrogen fluoride (HF). Recently, Higai et al 217 also reported a MAIL approach for direct graphite exfoliation, where 1-allyl-pyridinium-based ILs were used as the reaction medium. Irradiated by MW energy with the power of 300 W, the raw graphene was exfoliated into a few layers within 10 min.…”
Section: Synthesis Of Carbonsmentioning
confidence: 99%
“…The authors ascribed the success of the MAIL technique to the decomposition of PF 6 − -containing ILs accompanied by the generation of hydrogen fluoride (HF). Recently, Higai et al 217 also reported a MAIL approach for direct graphite exfoliation, where 1-allyl-pyridinium-based ILs were used as the reaction medium. Irradiated by MW energy with the power of 300 W, the raw graphene was exfoliated into a few layers within 10 min.…”
Section: Synthesis Of Carbonsmentioning
confidence: 99%